Physico-chemical quality and sensory evaluation of pummelo fruit as influenced by potassium fertilization - Magbalot-Fernandez, Alminda; De Guzman, Constancio C. (Annals of Tropical Research, 2021)
This study aimed to determine the influence of potassium (K) fertilization on the physico-chemical and sensory qualities of ‘Magallanes’ pummelo [Citrus maxima (Burm. Ex Rumph.) Merr.] fruit. The field experiment was conducted for 12 months at South Davao Corporation (SODACO) farm in Davao City. Five treatments with increasing K levels were applied per tree: control, no K, 150g K basal, 225g K basal, and 225g K basal + foliar application. The fruit physico-chemical qualities and sensory attributes were analyzed the following harvest. Data were analyzed using analysis of variance and honest significance difference tests. Application of 225g K rates positively influenced the fruit quality but not the sensory attributes of pummelo. Fruit pulp diameter increased by 36% while peel thickness decreased by 29-75%. An increase of 39% juice weight per fruit was obtained in 150g K. The yield of juice per tree increased up to 11 times with 225g K level. The 225g K rates also increased juice pH by 8-12%, titrable acidity by 9 times, and total soluble solids per tree by 6 times than no application. The application of 225g K basal + foliar resulted to higher fruit weight, TA, and TSS in pummelo fruit. The results of the study indicated the important role of K in improving the fruit physico-chemical qualities in ‘Magallanes’ pummelo.